Exploring voluntary sector specialist services for victim-survivors of sexual violence in England: the PROSPER co-production study - Caroline Bradbury-Jones; Sarah Damery; Kirsten Fruin; Clare Gunby; Jenny Harlock; Lucy Hebberts; Louise Isham; Anne-Marie Jones; Fay Maxted; Amelia Mighty; Priti Parmar; Laura Patterson; et al. (Health and Social Care Delivery Research)
Background There is increasing recognition in England that voluntary sector specialist sexual violence services are essential in providing crisis and longer-term support to victim-survivors. However, there is limited empirical evidence about the scope, range and effectiveness of voluntary sector specialist provision and commissioning, or what victim-survivors want from services. Objectives Explore victim-survivors’ experiences of accessing and using voluntary sector specialist services. Analyse the range, scope and funding of voluntary sector specialist services and how demand is managed. Explore the usefulness of different approaches to service delivery and different therapy models. Explore how different principles underlying service provision influence service delivery. Investigate referral patterns and pathways, and how voluntary sector specialist services fit with each other and link to the wider network of services for victim-survivors. Explore how arrangements for commissioning and funding services for victim-survivors across health, local authorities and criminal justice have evolved. Develop a taxonomy of the voluntary sector specialist services/service models being commissioned and provided. Make recommendations for the commissioning and provision of voluntary sector specialist services at practice and policy levels. Data sources Interviews with key stakeholders, focus groups with victim-survivors; a national survey of key stakeholders. Methods This multimethod study comprised five sequential work packages: work package 1: exploratory interviews with commissioners and providers and focus groups with victim-survivors; work package 2: national survey of service providers and commissioners; work package 3: in-depth case studies in four areas of England; work package 4: co-research with victim-survivors; work package 5: data integration. Co-production was built into the study from its inception through robust patient and public involvement and engagement activities. These included a co-applicant who is a survivor of sexual violence, plus the appointment of five expert-by-experience co-researchers. Results We captured the combined findings conceptually and diagrammatically into a new model comprising six themes: the complex and precarious funding landscape; the challenge of competition for funding and contracts; the importance and success of partnership working with organisations; the pressured environments within which voluntary sector specialist services work; different roles, scope and eligibility of voluntary and statutory services within an area; and the ways services are organised and delivered, underpinned by services’ values and philosophies. Limitations The COVID-19 pandemic meant that we were unable to use the proposed methods of data collection for the qualitative components. Mitigation was through developing online modes of data collection. Recruitment to the case study phase did not reach intended thresholds, but rich insights were drawn from earlier phases of the study. Conclusions The PROSPER study has provided hitherto missing evidence regarding the funding and commissioning of sexual violence services in England. The findings are likely to be useful in informing future commissioning of such services. The PROSPER study has also presented some unexpected opportunities for learning, particularly regarding co-research in the field of sexual violence. We also claim a contribution to theory development through the expansion of a current theoretical framework that may be of use to others working in the specialist voluntary sector. Future work The model will require development and testing to assess its usefulness as a resource for training and education or as an aid to communications in any interactions that are concerned with the delivery, funding and commissioning of voluntary sector specialist services. Study registration This study is registered as Research Registry researchregistry5144. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: 18/02/27) and is published in full in Health and Social Care Delivery Research; Vol. 13, No. 10. See the NIHR Funding and Awards website for further award information. Plain language summary Sexual violence is a sexual act against a person, or attempted act, that has not been agreed to. This may or may not include physical violence. In England and Wales, over half a million people experience sexual violence each year. More females than males experience sexual violence. The impacts for all people who experience sexual violence can be long-lasting and life changing. Often, people need a range of support services to help them recover. Many services, although now with paid staff, were started by and still use volunteers. These staff and volunteers understand a lot about sexual violence and they help many people. However, we do not know enough about where they are or what they do. We do not know how well they run their services or where their money comes from. We also do not know enough about what people using the services think about them. This research tried to answer these questions by speaking with people who provide the funding, people who work in the services and people who use the services. Some people who had experienced sexual violence were employed to help with the research. We found many differences in funding. Often, there is not enough money and organisations are trying to take the same ‘pot’ of money. Sometimes, those in control of the money do not know how best to spend it. Staff are sometimes unsure how to work with other services and are regularly stressed by a lot of people needing help. Those using sexual violence services had mixed experiences. How to access a service could be confusing and there were often long waiting lists. Many liked the special understanding that staff have about sexual violence. The research has helped us to make suggestions for improvements and will be widely shared to bring about change. Scientific summary Background Sexual violence (SV) is defined as any sexual activity or act that takes place without consent. In England and Wales, crime survey data indicate that over half a million people experience SV each year and the number who disclose to the police or seek support is increasing annually. More than 90% of victim-survivors are female. There is strong evidence that SV affects health, relationships, confidence, work and family life over the life course. In most parts of England, grassroots voluntary organisations have developed services in response to local needs. Although services vary from area to area, they often include crisis and longer-term counselling/therapy; telephone helplines; face-to-face advice; advocacy; play therapy for children; practical support in accessing other services; support groups and social and holistic activities. Most victim-survivors self-refer, while others are referred to voluntary sector specialist (VSS) SV services by a general practitioner (GP)/health/social care professional. VSS services sit alongside other local services for victim-survivors. In the last 12 years, there has been increasing national recognition in England that VSS services are essential in providing crisis and longer-term support to victim-survivors, enabling them to recover and thrive in the longer term. However, there is very little empirical evidence about the scope, range and effectiveness of VSS provision, or what victim-survivors value and want from services. There is no systematic review evidence and the few previous studies that exist are small scale and local. In addition, there is no literature on the effectiveness of different approaches to commissioning services for victim-survivors. There is also a paucity of evidence about the needs and experiences of staff working in VSS services, who can do so in a voluntary capacity. The aim of the study was to develop a comprehensive, national profile of VSS specialist services for victim-survivors in England, giving voice to service users’ experiences and using a comparative analysis of the range, scope and funding of services, victim-survivors’ service experiences, service models and approaches, service linkages and commissioning arrangements. The purpose was to make policy and practice recommendations to strengthen the overall service response to victim-survivors of SV. Objectives Explore victim-survivors’ experiences of accessing and using VSS services, identifying what needs are being met for which groups of victim-survivors and what encourages victim-survivors to take up services. Analyse the range, scope and funding of VSS services and how demand is managed. Explore the usefulness of different approaches to service delivery (including peer support and delivery by volunteers) and different therapy models. Explore how different principles underlying service provision influence service delivery, including feminist and trauma-informed principles of care. Investigate referral patterns and pathways, and how VSS services fit with each other and link to the wider network of services for victim-survivors. Explore how arrangements for commissioning and funding services for victim-survivors across health, local authorities and criminal justice have evolved over the last 3–5 years, and how they have impacted on VSS service provision. Develop a taxonomy of the VSS services/service models being commissioned and provided. Make recommendations for the commissioning and provision of VSS services at practice and policy levels, in order to strengthen overall service provision for victim-survivors of SV. Methods Co-production was built into the study from its inception through robust patient and public involvement and engagement activities. These included a co-applicant who is a survivor of SV, plus the appointment of five expert-by-experience co-researchers. The study was divided into the following work packages (WPs): WP1: exploratory interviews with commissioners and providers and focus groups with victim-survivors; WP2: national survey of service providers and commissioners; WP3: in-depth case studies in four areas of England; WP4: co-research with victim-survivors; WP5: data integration. We drew on Billis and Glennerster’s theory in relation to voluntary sector services as the underpinning framework. The theory identifies the unique features of voluntary sector services as: flatter organisational structures with less distance and distinction between senior or decision-making staff and those on the front line; closeness to communities; being mission-led and driven by core values and purpose. These three domains were relevant and appropriate in shaping our analysis. However, our findings went beyond values, communities and organisations, to include a broader commissioning context. We chose to adapt the theory and add a broader, macro level that encompassed the commissioning level/context. Data integration was thus achieved with reference to four theoretical domains: (1) macro commissioning context; (2) organisational structures; (3) relationships and people; (4) values and principles. Results Macro commissioning context: Overall, we found a complex (and precarious) funding landscape. It is a context in which national government and centralised funding policies are not reflecting local needs and the reality of demand. The study highlighted the challenges of competing for funding and contracts, where formal partnerships are viewed as beneficial from the commissioners’ perspective, and support VSS services to pool knowledge and resource and compete for bigger contracts. In the abscence of which, joint-funded, large contracts favour larger, often generic providers. This macro environment has impacts on victim-survivors, because the commissioning agenda acts to move services away from being truly victim-survivor led. Organisational structures: The study highlights the increasing range of VSS services providing therapeutic and practical support to victim-survivors through the commissioning process. A feature of this has been the ‘upskilling’ of staff to provide services to victim-survivors. In addition, there is clear evidence of services working closely with each other to support victim-survivors. However, from a less positive viewpoint, we identified a complex patchwork of services across statutory and VSS organisations that victim-survivors can struggle to naviagte. Within the VSS context, a concerning feature is the pressurised environment (e.g. high caseloads, rising demand, higher client need) and working with increasing complexity in clients’ lives. There is evidence that practitioners are leaving VSS services, with an attendant loss of specialism and expertise from the sector. In terms of service provision, we heard from practitioners and victim-survivors that there are problems with referral processes. We identified a contradictory pattern as regards the degree to which VSS services meet the needs of victim-survivors: there are unmet needs and under-represented groups, but this is balanced by examples of good links to support for under-represented populations. Relationships and people: We found that good relationships do exist between many statutory and voluntary sector services with examples of innovation and close partnership working. Most services work with a variety of commissioners, but there is varying satisfaction with these arrangements. From the viewpoint of victim-survivors, services can be hard to navigate and access. Moreover, uncertainties about waiting times can undermine victim-survivors’ trust and the perceived quality of support they receive. Values and principles: The study provides clear evidence that VSS services are highly valued by victim-survivors. VSS services offer a dedicated, protected environment for victim-survivors where the shame and stigma of SV are understood and challenged. Needs-led services are important, which focus on survivor empowerment. Feminist and trauma-informed approaches are valued within the VSS sector, a viewpoint that was shared across the participant groups. Gender awareness is also important, within a broad framework that takes account of intersectionality. From the perspective of VSS organisations, detailed understandings of sexual abuse constitute what it means to be a specialist, trauma informed service. We captured the combined findings conceptually and diagrammatically into a new model. It comprises six prominent themes: the complex and precarious funding landscape; the challenge of competition for funding and contracts; the importance and success of partnership working with organisations; the pressured environments within which VSS services work; different roles, scope and eligibility of voluntary and statutory services within an area; the ways services are organised and delivered, underpinned by services’ values and philosophies. Conclusions The PROSPER study has provided missing evidence regarding the funding and commissioning of VSS SV services in England. Even if the focus of future research is on VSS delivery (as is the case with much research in this field), it is likely that the wider lens of commissioning such services will have relevance. We claim a contribution to theory development through the expansion of a current theoretical framework that may be of use to others working in the VSS sector. The PROSPER study has also presented some unexpected opportunities for learning. At the forefront of these are the insights gained into co-research in the field of SV. We have presented transparent accounts of the strengths and limitations of this process. Core implications for policy, practice and education The study indicates the need for a sustainable funding framework for VSS services (e.g. a minimum 5-year funding period) with joined-up commissioning (and funding) from all statutory bodies whose services refer into specialist SV services. The findings highlight the need for contracts and grants to cover core service costs (e.g. contribution to employee pensions, sickness pay, rent, overheads, clinical supervision, etc.). In addition, innovation activities should be funded separately to core funding. It would be helpful for any statutory or non-statutory guidance issued by government to reflect this expectation. The findings indicate that VSS providers would benefit from being entrusted with greater autonomy and discretion in how they use allocated funding. VSS services know their local area and population and are the best placed to know where to allocate resource. Similarly, the study findings suggest that commissioners need to have the ability to operate flexibly as regards movement of funds to respond to local needs. The study findings show the importance of grants within the funding landscape and suggest that there should not be an exclusive focus on contracting/tendering services. We suggest that funding for grants should be increased substantially . We recommend that commissioners are trained (where they are not already) and supported to develop requisite specialism in the field of sexual and gender-based violence. They would be required to do so in other areas of specialist and clinical commissioning. This is crucial for the strategic and decision-making aspects of their role. Similarly, senior VSS practitioners need support and ‘upskilling’ to manage roles relating to grant funding and engaging with commissioners (e.g. training workshops, mentor relationships, etc.). Evidence from the study suggests the need for a closer relationship between commissioners and the services they fund, to ensure a greater understanding of the realities, complexities and needs of service provision. This could involve time spent shadowing within the VSS service. Based on the study findings, commissioners should support the development of local partnerships, through the allocation of funding, space to host meetings and facilitating introductions between key service staff. However, the study has also shown how partnerships work best when bottom-up and can develop without commissioners specifying who the key agency partners should be. The study findings point to the need for commissioners to commission services with a consideration of the needs of the workforce (competitive pay reflective of the trained workforce, resource to support staff training, job stability,, manageable workloads, to foster wellbeing and combat vicarious trauma). There is currently a disproportionate burden on commissioners and practitioners regarding reporting and monitoring requirements which needs to be reduced, for example, through use of similar/the same reporting/monitoring templates. What is considered 'good' in these key performance indicators must also be contextualised with an understanding of sexual violence recovery. Victim-survivors need ‘choice’ and different options at different time points. This study findings suggest that there needs to be recognition of the value of a range of VSS services – peer support, counselling, advocacy, etc. – and resistance to promoting overly medicalised models of support. The current focus on short-term counselling often fails to meet need and can overshadow other linked types of support (e.g. creative or systemic therapeutic work, political engagement, etc.). Sustainable, long-term design and organisation of services could help to eradicate the current hierarchies or ‘tiers’ that van exist within the VSS support system (i.e. referral pathways restricted by funding/criteria controls). This would mean that services can be accessed irrespective of how victim-survivors report/or to whom, how recent their experience of SV or based on demographic characteristics. Training of front-line health professionals (e.g. GPs, health visitors) is important as they are often the first entry/disclosure point to services, making it possible for health professionals to refer and signpost victim-survivors into specialist SV services. There is an opportunity to consider learning from pilot and/or localised schemes that are currently in operation in some areas of England. Recognition of the unique value of VSS services – and the different modalities that they offer – is currently patchy and the expertise of practitioners and senior leaders is not consistently understood amongst all commissioners and/or statutory services. There needs to be cultural change and a shifting of the recognition of what expertise ‘looks like’ when it comes to the provision of practical, therapeutic and social support for victim-survivors of SV. Victim-survivors (especially those from under-represented groups) need to be authentically involved in the decision-making around and development of SV services/provision. This should include involvement at various stages of the commissioning cycle. It should also include involvement at the points at which VSS services conceptualise/develop SV service provision. In addition to the recommendations relating to the empirical WPs on the PROSPER study, we also have some recommendations arising from the experiential, co-research work. Working with co-researchers Begin the process as early in the research cycle as possible. Avoid piecemeal co-production payments. Do not underestimate the power of in-person connection and support. Robust protocols, clear lines of communication and defined areas of responsibility need to be in place to manage and minimise destabilising incidents. Principal investigators are responsible for actively challenging and working against any systems that perpetuate victim-survivors’ silence. Principal investigators need to foster a culture of co-researchers being seen in ‘3D’, that is, seeing a co-researcher’s skill set beyond their lived experience. Research leaders and funders need to remain open to novel and unexpected benefits from research and respond to these in creative ways, so that insights are harnessed for future use. Research leaders and funders need to embrace the transformative and healing power of creativity – to recognise it as a credible area for financial investment. Critical reflection is crucial on how to embody intersectional approaches into co-research and the limitations associated with such attempts. Core implications for research The model that we have developed from the PROSPER findings will require development and testing to assess its usefulness as a resource for training and education in the VSS sector. Future studies can assess its potential as an aid to communications in any interactions that are concerned with the delivery, funding and commissioning of VSS services. It would be useful to expand the model by exploring the broad social impacts and how they relate to commissioning. This was not part of the PROSPER objectives and is missing from the current model. Future research would be useful to measure the full value of undertaking a co-researched study when the study participants are victim-survivors. This needs to be from the perspective of those taking part in the research. Study registration This study is registered as Research Registry researchregistry5144. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: 18/02/27) and is published in full in Health and Social Care Delivery Research; Vol. 13, No. 10. See the NIHR Funding and Awards website for further award information.